DAMPAK PENGETAHUAN KEUANGAN, SIKAP KEUANGAN DAN PENGENDALIAN DIRI TERHADAP PERILAKU KEUANGAN PEDAGANG IKAN DIPASAR BLAWI KARANGBINANGUN LAMONGAN - Moh. Ali Wafa; Moh. Azus Shony Azar (Politeknik Bisnis Indonesia, 2024)
The development of information that causes consumptive behavior so that consumers equate market prices with prices at cheaper online shops that occur with increased competition between traders so that traders are required to have good financial behavior amidst competition, consumptive, and technological developments.This study aims to examine the effect of financial knowledge, financial attitudes, and self-control variables on financial behavior variables. The population in this study were the market traders of Blawi Karangbinangun Lamongan. The sample selection in this study used a non-probability sampling technique, especially sensus sampling, which consisted of 92 fish seller and the data came from respondents by distributing questionnaires. The method used is multiple linear regression analysis.The results of this study indicate that financial knowledge has a positive and significant effect on financial behavior variables, financial attitudes have a positive and significant influence on financial variables, and self-control has a positive and significant effect on financial variables. Financial knowledge, financial attitudes, and self-control simultaneously affect financial behavior.